Kajian Antropolinguistik Nama Kedai Kopi di Wilayah Kemang, Jakarta Selatan - Fahmi Hidayat; Ahmad Khoiril Anam (LITERATUS, 2020)
In Jakarta, there are many coffee shops with unique names. It is also known that there is no possibility of meaning that is raised in the naming. A name will determine success and specifically attract an audience. The success in question is the success in obtaining the maximum profit from the business of the products offered. For this reason, the purpose of this research is to find out the meaning of naming a coffee shop in Kemang, South Jakarta. The method used is descriptive qualitative with anthropolinguistic perspective. The objects of this study were 40 coffee shops in Kemang, South Jakarta. The research instrument used was the researcher himself assisted by the meaning analysis table through observation and interviews. The results showed that of 40 coffee shops in Kemang, South Jakarta, as many as 40% or 16 coffee shops use futurative meanings for the naming, meaning that contains a hope in it.